Pengelolaan Laporan Keuangan Masjid Nurul Jihad Lingkungan Pangasa Kelurahan Samataring Kecamatan Sinjai Timur - Nirwana; Nurhayani; Jumardi; Ramli, Satria; Fajriani Azis (TEKNOVOKASI : Jurnal Pengabdian Masyarakat, 2023)
The preparation of financial reports is usually the responsibility of the managers or administrators of an organization when it has ended or will end. This is done to describe the situation and financial condition of the organization during that period. Likewise with the Babul Jihad mosque in the Pangasa Samataring Village environment which also requires financial reports. Based on observations made by researchers, the sources of mosque funds were obtained from charity boxes and donations, but the management of mosque financial reports in the Pangasa Environment did not yet have well-directed managers and management. Therefore, to overcome this problem is to provide a financial cash book that contains a list of income and expenses so that the mosque's financial system can be well-directed. With the aim that mosque administrators can present and provide relevant information regarding the financial position of the mosque as well as budget realization, cash flow, operating results and budget balances in the mosque. Especially in terms of procuring the management of mosque financial reports which previously did not exist due to the lack of knowledge of mosque administrators regarding financial reports. There are two methods used in overcoming this problem, namely facilitating mosque managers in the form of cash books and coaching in the form of how to use cash books to mosque managers. The results of the service show that after the service is held, the administrators of the Nurul Jihad mosque tend to understand more in managing financial reports as indicated by complete financial records.